What supports and limits learning in the early years? Listening to the voices of 200 children. Issue 2 (August 2018) - Flückiger, Bev; Dunn, Julie; Stinson, Madonna
This article reports on a study investigating young children's views about learning. The researchers engaged 200 Australian children from 3 to 8 years of age in conversations about how they liked to learn. In an attempt to privilege children's voices, the direct words of the participating children are used in the reporting of results. The children generated rich and thoughtful ideas about learning as well as factors contributing to their motivation and engagement in learning. Whereas Kindergarten children expressed a real sense of agency and self-efficacy in their learning, school-aged children expressed a strong desire for opportunities to be more actively engaged and have some control over their learning. Of concern was how quickly positive dispositions towards learning appeared to slide when children transitioned to school. The study challenges educators to find ways to listen to children in order to develop policies and practices that are responsive to children's perspectives and create school systems in which all children, without exception, are actively engaged, motivated and exercising agency in their learning.